Bloomberg Visual Guide to Candlestick Charting - Thomsett, Michael C. (Hoboken : John Wiley & Sons, 2012)
The easy-to-use guide to interpreting candlestick charts and derivative marketsCandlestick charts are an effective way of visualizing price movements and, due to the increased interest in the complex derivatives market, they are being used more and more widely. A combination of a line-chart and a bar-chart, where each bar represents the range of price movement over a given time interval, candlestick charts are most often used in technical analysis of equity and currency price patterns. A guide to the most used charts, The Candlestick Glossary is arranged in an easy-to-use manner, providing a q.
Chapter 8: Noncandlestick Confirmation Indicators and TermsAppendix: Bloomberg Functionality Cheat Sheet; Bibliography; Index.
Print version record.
Keywords: Stocks -- Charts, diagrams, etc; Investment analysis; Candlestick charts; Charts, diagrams, etc; Business; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investment analysis; Stocks; Electronic books; Charts, diagrams, etc